Generation of False Memory Using Real Life Setting - Khairudin, Rozainee (Faculty of Psychology, Universitas Surabaya, 2009)
Two experiments were conducted in this study: Experiment 1 investigated whether subjects were misled by leading questions when remembering a mugging event. Thirty police recruits partici- pated as subjects. Subjects‟ memory was tested immediately after they observed a staged mugging event. The results of Experiment 1 showed that subjects were easily suggestible to misleading questions about the mugging event. Experiment 2 used a face recognition test. Sixty police recruits participated in Experiment 2. The results showed that there was no significant effect of the instruc- tion factor (warning/without warning) or the time after which subjects were tested (immediately/a week after). However, there was a significant interaction between the two factors. Subjects were more affected by the warning instructions only when they were tested a week after watching the staged event. Findings are discussed in relation to memory theories and the validity of eyewitness testimony. Dua eksperimen dilakukan dalam studi ini. Eksperimen 1 meneliti apakah para subjek terkecoh pertanyaan penuntun ketika mengingat kejadian perampokan. Tiga puluh anggota polisi berpartisi- pasi sebagai subjek. Ingatan subjek diuji segera setelah mereka menyaksikan adegan kejadian pe- rampokan. Hasil Eksperimen 1 menunjukkan bahwa para subjek mudah tersugesti pertanyaan pengecoh tentang kejadian perampokan tersebut. Eksperimen 2 menggunakan uji pengenalan wa- jah. Enam puluh anggota polisi berpartisipasi dalam Eksperimen 2. Hasil menunjukkan bahwa tak ada akibat signifikan dari faktor instruksi (peringatan/tanpa peringatan) atau waktu setelah para subjek diuji (segera/seminggu kemudian). Namun, terdapat interaksi signifikan antara kedua fak- tor. Para subjek lebih terpengaruh instruksi peringatan hanya bila mereka diuji seminggu setelah menyaksikan adegan perampokan tersebut. Temuan dibahas dalam kaitan dengan teori ingatan dan validitas kesaksian saksi mata.